Making a good impression - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
After the writing and illustrating is over, it s all down to reproducing the original. Work out as closely as possible the number of copies you will need and which you will be able to distribute during your document s life; Remember that...